THE IMMUNOLOGICALLY DEPENDENT PRINCIPLES OF THE PATHOGENESIS OF THE CHRONIC HEART FAILURE (OVERVIEW OF LITERATURE). - Курилів, Г. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The state represents the review of literature, devoted the problem of chronic heart failure. The attention was attraced to the modern ways of pathogenesis of the chronic heart failure. It was educed that the majority of investigations were connected with immune-inflammatory mecanisms, especially the activation of cytokines, factors of grows, neopterin. This substances influence on the endotheliocytes and cardiomyocytes, beginning the development of the endothelium disfunction and then the chronic heart failure.